Interaction of seed dispersal and environmental filtering affects woody encroachment patterns in coastal grassland. Issue 7 (16th July 2019) - Woods, Natasha N.; Dows, Benjamin L.; Goldstein, Evan B.; Moore, Laura J.; Young, Donald R.; Zinnert, Julie C.
Abstract: Encroachment of woody plants into grasslands has occurred worldwide and includes coastal ecosystems. This conversion process is mediated by seed dispersal patterns, environmental filtering, and biotic interactions. As spatiotemporally heterogeneous, harsh environments, barrier islands present a unique set of challenges for dispersal and establishment. Environmental conditions act as filters on dispersed seeds, thereby influencing encroachment and distribution patterns. Seldom have patterns of propagule dispersal been considered in the context of woody encroachment. We quantified dispersal and post‐dispersal processes of an encroaching woody population of Morella cerifera relative to directional rate of encroachment and observed distribution patterns on an Atlantic coastal barrier island with strong environmental filtering. We analyzed historic foredune elevation as a proxy for reduced interior environmental stress. The dispersal kernel was leptokurtic, a common characteristic of expanding populations, but rate of encroachment has slowed since 2005. Expansion pattern was related to foredune elevation, which limits encroachment below a threshold elevation. This difference between dispersal kernel behavior and encroachment rate is due to limited availability of suitable habitat for Morella and temporal variability in chlorides during the time of germination. Our results demonstrate that processes mediating seeds and seedling success must be accounted for to better understand establishment patterns of encroaching woody plants.